Interpretation of Legal Norms in Modern Jurisprudence: Theoretical and Practical Aspects of Human Rights Protection Under Martial Law - Sydorov, Yaroslav; Yurchenko, Vasyl; Kantor, Nataliia; Chekhovych, Tetiana; Dietochka, Anatolii (Jurnal Cita Hukum, 2025)
The purpose of the research is to consider ways for the interpretation of legal norms in modern jurisprudence. Main content. It has been established that interpretation will result in a general conclusion or a sum of the findings reached by the subject of interpretation in the process of clarifying the rule of law (legal norms) using the entire set of interpretation methods, which is adequate to the actual content of this rule and meets the criteria of truth and correctness of the result of interpretation... Methodology: The methodological basis of the research is presented as comparative-legal and systematic analysis, formal-legal method, interpretation method, hermeneutic method, as well as methods of analysis and synthesis. Conclusions. It has been concluded that the procedure for achieving the goal of interpretation should be as follows: grammatical interpretation, teleological interpretation - clarification of compliance of the essence of legal norm content with the principles of law, systematic interpretation, special legal interpretation, logical interpretation, functional interpretation, historical interpretation - repeated application of the interpretation procedure when receiving new data. REFERENCES: Antoshkina, Valeriia Kostiantynivna. 2011. Reasons for the interpretation of civil law norms: Actual problems of civil law: the materials of the "round table" are dedicated. in memory of Prof. Genghis Khan by Nufatovych Asimov. National Law Academy of Ukraine named after Yaroslav the Wise. Right. Kharkiv. Ukraine. BEZPALOVA, Olha. YUNINA, Maryna. KOROHOD, Svitlana. REZVOROVICH, Kristina. OHANISIAN, Tsahik. 2021. Legal regulation of entrepreneurial activity in the national security system. Entrepreneurship and Sustainability Issues, 8(3), 340-355. DOI:10.9770/jesi.2021.8.3(22) Halaburda, Nadiia. Leheza, Yevhen, Chalavan, Viktor. Yefimov, Volodymyr. Yefimova, Inna. 2021. Compliance with the principle of the rule of law in guarantees of ensuring the legality of providing public services in Ukraine. Journal of law and political sciences. Vol. 29, Іssue 4, 100-121. Kobrusieva, Yevheniiа. Leheza, Yevhen. Rudoi, Kateryna. Shamara, Oleksandr. Chalavan, Viktor. 2021. International standards of social protection of internally displaced persons: administrative and criminal aspects. Jurnal cita hukum indonesian law journal. Vol 9, No 3, 461-484. DOI: https://doi.org/10.15408/jch.v9i3.23752 Kotiuk, Volodymyr Oleksandrovych. 1996. Theory of law: educational. Ventur. Kyiv. Ukraine. Kudlai, Tamara Pavlivna. 2009. Theory of the state and law: study guide / T.P. Kudlai NADU, Kyiv. Ukraine. Kulinich, Olha. Leheza, Yevhen. Zadyraka, Nataliia. Taranenko, Kseniia, Kostiuk, Tetiana. 2023. Electronic Judicial Procedure as an Element of Access to Justice Regarding Protection of Rights of Individuals: Legal, Administrative, Theoretical, and Informational Aspects. Jurnal cita hukum indonesian law journal. 11 (3), 443–456. DOI: https://doi.org/10.15408/jch.v11i3.36298 Leheza, Y., Kolomoiets, Y., Chalyk, V., Kovalchuk, Y., & Sakhno, A. (2024). Foreign experience of financial-legal and administrative legal regulation of the activities of public administration bodies. Revista do Curso de Direito do UNIFOR, 15(1), 51–60. DOI: https://doi.org/10.24862/rcdu.v15i1.1832 Leheza, Y., Korniienko, M.., Berezniak, V., Мariienko А., & Radchuk, A. (2024). Legal Regulation of Liability for Illegal Deportation of Children: Administrative, Criminal Aspects, Experience of Ukraine and International Standards. Revista Jurídica Portucalense, 257–274. https://doi.org/10.34625/issn.2183-2705(36)2024.ic-11 Leheza, Y., Shcherbyna, Bogdan. Leheza, Yulia. Pushkina, Olena & Marchenko, O. (2023). “Features of Applying the Right to Suspension or Complete/ Partial Refusal to Fulfill a Duty in Case of Non-Fulfilment of the Counter Duty by the Other Party According to the Civil Legislation of Ukraine.” Revista Jurídica Portucalense, 340–359. Retrieved from https://revistas.rcaap.pt/juridica/article/view/29662 Leheza, Yevhen. Filipenko, Tatiana. Sokolenko, Olha. Darahan, Valerii, Kucherenko, Oleksii. 2020. Ensuring human rights in Ukraine: problematic issues and ways to address them in the social and legal sphere. Cuestiones políticas. Vol. 37 № 64 (enero-junio 2020). P. 123-136. DOI: https://doi.org/10.46398/cuestpol.3764.10 Leheza, Yevhen. Pisotska, Karina. Dubenko, Oleksandr. Dakhno, Oleksandr. Sotskyi, Artur. “The essence of the principles of Ukrainian law in modern jurisprudence”. Revista jurídica portucalense, December (2022): 342–363. https://doi.org/10.34625/issn.2183-2705(32)2022.ic-15 Leheza, Y. Shcherbyna, Bogdan. Leheza, Yulia. Pushkina, Olena. Marchenko, Olesia. (2024). Características de la suspensión o de la denegación, total o parcial, del cumplimiento de una obligación en caso de incumplimiento de la contraparte, según la legislación civil ucraniana. Novum Jus, 18(2), 131–150. https://doi.org/10.14718/NovumJus.2024.18.2.5 Leheza, Y. Yerofieienko, Larysa. Komashko, Volodymyr. (2023). Propiedad intelectual en Ucrania bajo la ley marcial: regulación jurídica, aspectos administrativos y civiles. DIXI, 26(1), 1-11. https://doi.org/10.16925/2357-5891.2024.01.09 URL. https://revistas.ucc.edu.co/index.php/di/article/view/4960 Leheza, Yevhen. Yurovskа, Viktoriia. Zamryha, Artur. Ulozhenko, Vadym, Bohdan. Bohdana 2024. Administrative and legal regulation of the status of internally displaced persons in Ukraine during the war. University of Western Australia Law Review. 51 (2). 297-313. https://www.uwa.edu.au/schools/-/media/documents/uwa-law-review/volume-51-issue-2/leheza-et-al-formatted.pdf Matviichuk, Anatolii. Shcherbak, Viktor. Sirko, Viktoria. Malieieva, Hanna. Leheza, Yevhen. 2022. Human principles of law as a universal normative framework: Principios humanos del derecho como marco normativo universal. Cuestiones Políticas, 40(75), 221-231. https://doi.org/10.46398/cuestpol.4075.14 Mykhailovych, Dmytro Marianovych. 2003. Official interpretation of the law: abstract of the dissertation for obtaining the scientific degree of candidate of legal sciences. Kharkiv National University of Internal Affairs. Ukraine. Nalyvaiko, Larysa Leheza, Yevhen, Sachko, Oleksandr. Shcherbyna, Victor. Chepik-Trehubenko. Olha. 2022. Principles of law: Methodological approaches to understanding in the context of modern globalization transformations. Ius Humani. Law Journal, 11(2), 55-79. https://doi.org/https://doi.org/10.31207/ih.v11i2.312 Patei-Bratasiuk, Mariia Hryhorivna. 2010. Anthropocentric theory of law: a study guide. Kyiv. Ukraine. Sinkevych, O., YurovskаV., Komissarova, N., Tkachenko, O., & Leheza, Y. (2024). Subjects of public authority in matters of combating terrorism: legal regulation, administrative, and criminal aspects. Ius Humani. Law Journal, 13(1), 1-14. https://doi.org/10.31207/ih.v13i1.332 Skakun, Olha Fedorivna. 2012. Theory of law and the state: a textbook. Alert. Kyiv. Ukraine. Tylchyk, Vyacheslav. Matselyk, Tetiana. Hryshchuk, Viktor. Lomakina, Olena. Sydor, Markiian. Leheza, Yevhen. 2022. Administrative and legal regulation of public financial activity: Regulación administrativa y legal de la actividad financiera pública. Cuestiones Políticas, 40(72), 573-581. https://doi.org/10.46398/cuestpol.4072.33 Villasmil Espinoza, Jorge; Leheza, Yevhen; Holovii, Liudmyla. 2022. Reflections for the interdisciplinary study of the Russian Federation’s invasion of Ukraine in 2022: Reflexiones para el estudio interdisciplinario de la invasión de Ucrania por parte de la Federación Rusa en 2022. Cuestiones Políticas, 40(73), 16-24. https://doi.org/10.46398/cuestpol.4073.00 Volynka, Kateryna Hryhorivna. 2003. Theory of the state and law: a study guide. MAUP. Kyiv. Ukraine. Zadyraka, Nataliia. Leheza, Yevhen. Bykovskyi, Mykola. Zheliezniak, Yevhenii. Leheza, Yulia. 2023. Correlation of Legal Concepts of Administrative Procedure and Administrative Liability in the Sphere of Urban Planning. Jurnal cita hukum indonesian law journal. Vol. 11 No. 1, pp. 33–44, DOI: https://doi.org/10.15408/jch.v11i1.31784